On the use of side-chain NMR relaxation data to derive structural and dynamical information on proteins: A case study using Hen Lysozyme - Smith, LJ; van Gunsteren, WF; Hansen, N (Wiley, 2020)
Values of S2CH and S2NH order parameters derived from NMR relaxation measurements on proteins cannot straightforwardly be used to determine protein structure, because they cannot be related to a single protein structure, but are defined in terms of an average over a conformational ensemble. MD simulation can generate a conformational ensemble and thus be used to restrain S2CH and S2NH order parameters towards experimentally derived target values S2CH(exp) and S2NH(exp). Application of S2CH and S2NH order‐parameter restraining MD simulation to bond vectors in 63 side chains of the protein hen egg white lysozyme using 51 S2CH(exp) target values and 28 S2NH(exp) target values shows that a conformational ensemble compatible with the experimentally derived data can be obtained using this technique. It is observed that S2CH order‐parameter restraining of C‐H bonds in methyl groups is less reliable than S2NH order‐parameter restraining, because of possibly less valid assumptions and approximations used to derive experimental S2CH(exp)‐values from NMR relaxation measurements and the necessity to adopt the assumption of uniform rotational motion of methyl C‐H bonds around their symmetry axis and of the independence of these motions from each other. The restrained simulations demonstrate that side chains on the protein surface are highly dynamic. Any hydrogen bonds they form and that appear in any of four different crystal structures, are fluctuating with short lifetimes in solution.